Transfer of Infectious Drug Resistance in Microbially Defined Mice - Reed, Norman D. (1969)
Germ-free mice were intentionally associated with drug-resistant donor strains of Escherichia coli known to carry R factors and with drug-sensitive recipient strains. In vivo transfer of R factors was observed in all experiments, involving five different donor-recipient combinations. The number of converted recipients varied, depending upon the donor-recipient combination, but in all cases it was restricted by limiting numbers of either recipient or donor strains in the digestive tract of the microbially defined mice. Converted recipients were detected in fecal material as early as 5.5 hr after mice were associated with donor and recipient bacteria. Donors, recipients, and converted recipients were detectable in the stomach, small intestine, cecum, and large intestine of the microbially defined mice and their suckling young.